Towards Sustainable Freight Transportation - A Risk Framework Application to Truck Platooning - Münch, Christopher; Benz, Lukas; Hartmann, Evi (Logistics Management, 2021)
National and international authorities, specifically the European Commission, have set challenging targets for the reduction of carbon emissions. Transportation is an important lever for emission reduction due to the share of over one quarter of the total emissions in Europe. In particular, road transportation, which accounts for 75% of the transported goods, offers saving potential. The improvement of traffic flows has been identified as a field for prospective energy consumption reduction, among others, by automation, especially platooning. Truck platooning has been discussed from a technical perspective, as well as with a focus on advantages. Risks have so far been included by some authors but not examined holistically. To close this research gap, a case study was conducted in this article to investigate the risks associated with platooning. For this purpose, eight semi-structured interviews were conducted with experts from logistics service providers and truck manufacturers. Eighteen risks were identified and classified into six dimensions (economic, social, legal, IT-related, technical, and ecological), resulting in a risk framework. The results extend the research on truck platooning by clarifying the risk perspective of this concept and provide a starting point for a discussion on the feasibilit